2014
DOI: 10.1186/s12913-014-0578-1
|View full text |Cite
|
Sign up to set email alerts
|

Duration of participation in continuous quality improvement: a key factor explaining improved delivery of Type 2 diabetes services

Abstract: BackgroundIt is generally recognised that continuous quality improvement (CQI) programs support development of high quality primary health care systems. However, there is limited evidence demonstrating their system-wide effectiveness. We examined variation in quality of Type 2 diabetes service delivery in over 100 Aboriginal and Torres Strait Islander primary health care centres participating in a wide-scale CQI project over the past decade, and determined the influence of health centre and patient level facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 16 publications
5
47
0
1
Order By: Relevance
“…First, that CQI interventions need to be implemented for an adequate duration to effect change in primary care settings is shown here, supported by other recent studies applying CQI processes 19, 24. Second, this evaluation illustrates the critical importance of cultural competence within health systems, especially when tackling diseases of disparity such as RHD, which predominantly affects Indigenous and disadvantaged populations globally.…”
Section: Discussionsupporting
confidence: 75%
“…First, that CQI interventions need to be implemented for an adequate duration to effect change in primary care settings is shown here, supported by other recent studies applying CQI processes 19, 24. Second, this evaluation illustrates the critical importance of cultural competence within health systems, especially when tackling diseases of disparity such as RHD, which predominantly affects Indigenous and disadvantaged populations globally.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, as data are collected from client records, service delivery may be underestimated due to poor documentation. We are also aware that services who have participated in three or more consecutive annual audits are possibly more committed to reviewing the quality of the care they deliver than those that did not participate and therefore may be generally better performing …”
Section: Discussionmentioning
confidence: 99%
“…We are also aware that services who have participated in three or more consecutive annual audits are possibly more committed to reviewing the quality of the care they deliver than those that did not participate and therefore may be generally better performing. 13 Does involvement in regular CQI activities lead to better services or do better services participate in regular CQI activities? These questions are for further investigation in our child health data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous Quality Improvement (CQI) aims to facilitate ongoing improvement in the quality of primary care by using objective information to analyze and improve systems, processes, and outcomes (6). The evidence for the effectiveness of CQI is mixed and context dependent (7, 8); however, studies have shown that in some settings, it can be effective in improving quality of care (9), professional practice (10), and patient outcomes (11), particularly when used over longer periods of time (12). …”
Section: Introductionmentioning
confidence: 99%